Different approaches to model the nearshore circulation in the south shore of O'ahu, Hawaii - J. M. Azevedo Correia de Souza; B. Powell (Ocean Science, 2017)
The dynamical interaction between currents, bathymetry, waves, and estuarine outflow has significant impacts on the surf zone. We investigate the impacts of two strategies to include the effect of surface gravity waves on an ocean circulation model of the south shore of O'ahu, Hawaii. This area provides an ideal laboratory for the development of nearshore circulation modeling systems for reef-protected coastlines. We use two numerical models for circulation and waves: Regional Ocean Modeling System (ROMS) and Simulating Waves Nearshore (SWAN) model, respectively. The circulation model is nested within larger-scale models that capture the tidal, regional, and wind-forced circulation of the Hawaiian archipelago. Two strategies are explored for circulation modeling: forcing by the output of the wave model and online, two-way coupling of the circulation and wave models. In addition, the circulation model alone provides the reference for the circulation without the effect of the waves. These strategies are applied to two experiments: (1) typical trade-wind conditions that are frequent during summer months, and (2) the arrival of a large winter swell that wraps around the island. The results show the importance of considering the effect of the waves on the circulation and, particularly, the circulation–wave coupled processes. Both approaches show a similar nearshore circulation pattern, with the presence of an offshore current in the middle beaches of Waikiki. Although the pattern of the offshore circulation remains the same, the coupled waves and circulation produce larger significant wave heights ( ≈  10 %) and the formation of strong alongshore and cross-shore currents ( ≈  1 m s−1).